Impact of a heterogeneous environment on the population expansion of the harmful plant Iris ruthenica Ker-Gawl. in the high mountain grasslands - Tayier, Gulinige; Hasimu, Dilixiati; Aishan, Tayierjiang; Yimingniyazi, Amanula (Frontiers in Plant Science, 2024)
Iris ruthenica Ker-Gawl. (Russian iris) is a perennial, clonal, herbaceous plant that is spread across the degraded mountain grasslands in northern Xinjiang. In this study, to explore the breeding system and the impact of slope orientation on the flowering phenology, pollination characteristics, and other aspects of I. ruthenica, we used a combination of field observations and controlled experiments to compare the population density, flowering phenology, floral characteristics, breeding system, and pollinator type and behavior of plants on different slope orientations. Vegetation coverage on the north (N), southwest (SW), and southeast (SE) slopes was 90%, 67%, and 53%, respectively. Differences in plant height and diameter were observed between the SE slope and the N and SW slopes, whereas the N and SW slopes were similar in these respects. The SE slope exhibited the earliest initial flowering time, followed by the SW and N slopes. The diameter of the corolla, distance between the stigma and anther, length of the anther and ovary, number of pollen grains, and number of ovules on the N slope were smaller than those on the SE and SW slopes, whereas those of the SE and SW slopes were similar.Artificial pollination experiments showed that neither bagging nor unbagging resulted in seed formation after emasculation for all slope orientations. The pollinating insects of I. ruthenica included Bombus sp., Amegilla leptocoma, Andrena sp., and Halictus sp.; the types and numbers of pollinating insects differed among slopes. In summary, on SE and SW slopes with high temperatures and sufficient sunlight, this species attracted pollinators and provided them with more opportunities to visit and pollinate by flowering early, with large numbers of blooms, and a longer flowering period and lifespan, ensuring successful reproduction. Under unfavorable conditions, such as insufficient pollinators and limited activity caused by the more stressful environmental conditions of the N slope (including low temperature and insufficient light), this species ensures a certain seed yield by increasing its self-compatibility.